TRAINING ANALYSIS IN IMPROVING EMPLOYEE COMPETENCY AT PT VANAYA CENDEKIA SOUTH JAKARTA - Agrasadya, Agrasadya; Sunarto, Ading; Apriansyah, Muger (Yayasan Education and Social Center, 2024)
This research aims to learn about analytical Training influencing employee competence at PT. Vanaya Scholar South Jakarta. The research method used is a qualitative type of research using a sampling technique, namely purposive sampling. This research uses SWOT analysis techniques, observation and direct interviews with key informants and informants. The results of this research indicate that employees at PT routinely carry out Training. Vanaya Scholar South Jakarta has had both positive and negative Training. Positive Training is routinely carried out on a predetermined schedule for each employee. The negative Training that is available is that much of it has yet to be implemented during operations, and the manager's role is to supervise employees. If there are employees who work without using SOP procedures and MUI Halal procedures, they will be subject to sanctions. The sanctions given to employees trigger employees to be more responsible and work using SOP and MUI Halal procedures. The factor that influences Training on employee competency is the need for rewards and recognition for employees. Efforts to increase employee competency are successful, and they involve regular Training so that they can do all the work as expected by the company without feeling that the work is a burden to them, which increases the company's turnover. The company can provide employee welfare